Sea Turtles Conservation Centre with Ecological Architecture Approach - Andalucia Andalucia; Nur Aprinela Kasra (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Turtles are integral components of two ecosystems, both coastal and marine. They play a crucial role in maintaining a healthy marine ecosystem. A nutritious sea fosters millions of fish, serving as a significant protein source for humans. However, this is increasingly at odds with the presence of turtles, which are gradually becoming endangered. This issue stems from various factors, including large-scale commercial fishing activities near turtle nesting sites and worsening climatic changes. These factors have the potential to disrupt the balance of marine ecosystems. The approach adopted in this design is an ecological architecture approach. It aims to restore turtle habitats in coastal conservation areas to attract nesting turtles and sustainably develop tourist facilities that harmonize with the surrounding environment.